Psychocultural Mechanisms of the Propensity toward Criminal Homicide: A Multidimensional View of the Culture of Honor - Souza, Monica G. T. C.; Souza, Bruno C.; Roazzi, Antonio; Silva, Edson S. da (Frontiers in Psychology, 2017)
Introduction: Theory of the Culture of Honor is one of the few models in criminology specifically geared towards homicide. It proposes that, in certain societies, men must never show weakness and are required to react violently to any perceived threats to their reputation, thereby increasing their probability of committing a homicide. This has been suggested as the main explanation for the high rates of this type of crime in Brazil, particularly in the Northeast. Underlying this explanation there are complex mechanisms and processes that have yet to be clarified. Objectives: The present research aimed to investigate the workings of the possible psychocultural mechanisms underlying the culture of honor and the process through which they might affect the individual propensity towards homicide. Method: A total of 336 Brazilian adults were assessed regarding a broad range of sociodemographic, psychological, and sociocultural variables, including their attitudes towards homicide. The resulting dataset was analyzed using Smallest Space Analysis and Facet Theory. Results: It seems that certain cultural elements associated to traditional masculinity and enhanced anger tend to promote negative personality traits and increase one’s propensity towards committing homicide. Conclusions: The findings obtained not only confirm the Theory of the Culture of Honor for the propensity towards homicide, but also explicit and clarify some of the psychocultural processes and mechanisms involved, suggesting a new scientific framework.